Global Inequalities in Cervical Cancer Incidence and Mortality are Linked to Deprivation, Low Socioeconomic Status, and Human Development - Gopal K. Singh, PhD; Romuladus E. Azuine, DrPH, RN; Mohammad Siahpush, PhD (Global Health and Education Projects, Inc., 2016)
Objectives This study examined global inequalities in cervical cancer incidence and mortality rates as a function of cross-national variations in the Human Development Index (HDI), socioeconomic factors, Gender Inequality Index (GII), and healthcare expenditure. Methods Age-adjusted incidence and mortality rates were calculated for women in 184 countries using the 2008 GLOBOCAN database, and incidence and mortality trends were analyzed using the WHO cancer mortality database. Log-linear regression was used to model annual trends, while OLS and Poisson regression models were used to estimate the impact of socioeconomic and human development factors on incidence and mortality rates. Results Cervical cancer incidence and mortality rates varied widely, with many African countries such as Guinea, Zambia, Comoros, Tanzania, and Malawi having at least 10-to-20-fold higher rates than several West Asian, Middle East, and European countries, including Iran, Saudi Arabia, Syria, Egypt, and Switzerland. HDI, GII, poverty rate, health expenditure per capita, urbanization, and literacy rate were all significantly related to cervical cancer incidence and mortality, with HDI and poverty rate each explaining >52% of the global variance in mortality. Both incidence and mortality rates increased in relation to lower human development and higher gender inequality levels. A 0.2 unit increase in HDI was associated with a 20% decrease in cervical cancer risk and a 33% decrease in cervical cancer mortality risk. The risk of a cervical cancer diagnosis increased by 24% and of cervical cancer death by 42% for a 0.2 unit increase in GII. Higher health expenditure levels were independently associated with decreased incidence and mortality risks. Conclusions and Public Health Implications: Global inequalities in cervical cancer are clearly linked to disparities in human development, social inequality, and living standards. Reductions in cervical cancer rates are achievable by reducing inequalities in socioeconomic conditions, availability of preventive health services, and women's social status. Key Words: Cervical cancer • Incidence • Mortality • Global inequality • Human development • Gender inequality • Social inequality • Poverty • Literacy • GNI per capita.